Basics for breeding native bees: feeding and multiplication (Research, Society and Development, 2020)
Meliponines are important pollinators of tropical forest species, and an interesting feature of these is the possibility of their creation rationally. The present review highlights the importance of native bees and key points that can boost breeding. Despite its importance to the ecosystem, there are factors that have contributed to the reduction of bees, among them, the intensive occupation of the environment by man, causing impacts through the elimination of food sources. Like any other organism, bees need nutrients for their growth and its scarcity has harmful effects on the development of colonies. Despite its importance the study of artificial diets that can supply the needs of the bees in periods of low availability of food are still insufficient. To supply the lack of nectar one can look for the supply of an energetic food based on the mixture of water and sugar, however there are few studies aiming at the elaboration of protein supplements that can replace the pollen. Studies with complementary supplements enable creators to increase their creation through division and multiplication of colonies. However there is a lack of techniques that would allow the growth and increase of meliponicola production in the country.